2016
DOI: 10.1038/cddis.2016.219
|View full text |Cite
|
Sign up to set email alerts
|

PGA1-induced apoptosis involves specific activation of H-Ras and N-Ras in cellular endomembranes

Abstract: The cyclopentenone prostaglandin A1 (PGA1) is an inducer of cell death in cancer cells. However, the mechanism that initiates this cytotoxic response remains elusive. Here we report that PGA1 triggers apoptosis by a process that entails the specific activation of H- and N-Ras isoforms, leading to caspase activation. Cells without H- and N-Ras did not undergo apoptosis upon PGA1 treatment; in these cells, the cellular demise was rescued by overexpression of either H-Ras or N-Ras. Consistently, the mutant H-Ras-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Cyclopentenone prostaglandins such as PGA1 and PGA2 have been found to inactivate p53-dependent transcription and induce p53-independent apoptotic cell death ( Lee et al, 2020 ). More specifically, PGA1 appears to induce apoptosis in mammalian cells by specifically binding to H- and N-Ras on endomembranes and activating them ( Anta et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclopentenone prostaglandins such as PGA1 and PGA2 have been found to inactivate p53-dependent transcription and induce p53-independent apoptotic cell death ( Lee et al, 2020 ). More specifically, PGA1 appears to induce apoptosis in mammalian cells by specifically binding to H- and N-Ras on endomembranes and activating them ( Anta et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins reinforce senescence via positive ras/ p53 feedback H-RAS is activated by exogenous 15d-PGJ2 at 3-5 mM (Oliva et al, 2003), roughly the dihomo-15d-PGJ2 level at which senescent cells and other cyclopentenone prostaglandins activate other RAS isoforms or similar GTPases (Anta et al, 2016;Renedo et al, 2007;Wall et al, 2015). We hypothesized that constitutive RAS activation might drive senescence in response to the elevated dihomo-15d-PGJ2.…”
Section: Prostaglandins Promote Senescent Phenotypesmentioning
confidence: 96%
“…This finding corroborates other studies in nongestational tissues which have found overexpression of Ras under other inflammatory conditions such as in cancers [ 48 50 ], cigarette smoking [ 51 ], diabetes, and obesity [ 52 , 53 ]. In addition to inflammation, apoptotic signals can also activate Ras [ 54 ]. Although beyond the scope of the current study, the effects on placental Ras expression following exposure to apoptosis markers such as caspases or PARP (a marker of repair and cell death) warrants further study.…”
Section: Discussionmentioning
confidence: 99%